Nutritional potassium limitation impact on serum potassium change, and death in chronic kidney disease: A meta‐analysis - Gong, Zhumei; Chen, Taiai (Therapeutic apheresis and dialysis, 2022)
Introduction We performed a meta‐analysis to evaluate the impact of nutritional potassium limitation on serum potassium change, and death in chronic kidney disease. Methods A systematic literature search up to October 2021 was carried out and eight studies included 92 558 subjects with chronic kidney disease at the start of the study; 41 474 of them were provided with nutritional potassium limitation and 510 084 were nonrestricted diet. Results Nutritional potassium limitation had significantly lower serum potassium change (MD, −0.33; 95% CI, −0.58 to −0.07; p = 0.01) compared to nonrestricted diet in subjects with chronic kidney disease. However, nutritional potassium limitation had no significant impact on the death (OR, 0.80; 95% CI, 0.58–1.10; p = 0.17) compared to nonrestricted diet in subjects with chronic kidney disease. Conclusion Nutritional potassium limitation had significantly lower serum potassium change compared to nonrestricted diet in subjects with chronic kidney disease. Further studies are required to validate these findings.